Technological trends in the medical devices industry and related healthcare - Izsak, Kincsö,Terrier, Apolline (European Commission, 2020)
This sectoral report has been prepared in the framework of the 'Advanced Technologies for Industry' (ATI) project. It analyses trends in the generation and uptake of advanced technologies, entrepreneurial activities and skills supply and demand in the medical devices industry, and secondly, it also explores trends in the related healthcare sector from a demand-side perspective. The analysis interprets data from a list of sources compiled to monitor advanced technologies and their applications in industry across Europe and key competitor economies. Medical devices are defined as any apparatus, appliance, software or material, which is used for the diagnosis, prevention, monitoring, or treatment of diseases, injury or disability1. Besides medical devices, it also discusses the related use and uptake of digital technologies in the healthcare sector. The starting point of this analysis has been 16 advanced technologies that are a priority for European industrial policy and that enable process, product and service innovation throughout the economy and hence foster industrial modernisation. Advanced technologies are defined as recent or future technologies that are expected to substantially alter the business and social environment and include advanced materials, advanced manufacturing, artificial intelligence, augmented and virtual reality, big data, blockchain, cloud technologies, connectivity, industrial biotechnology, Internet of Things, micro and nanoelectronics, mobility, nanotechnology, photonics, robotics, security. The relevance of these specific technologies in the medical devices industry has been explored through patent analysis and data on private equity investments, skills and technology uptake. The full methodology behind the data calculations is available here: This report is structured as the following: - The first section sets the industrial context. - The second section analyses technological trends in advanced technologies applied in the medical devices industry based on patents and text-mining of company websites. - The third section presents findings about private equity investment and startup/spinoff activity. - The fourth section explores the supply and demand of skills related to advanced technologies. - The fifth chapter concludes with a short future outlook.
10.2826/162267
Keywords: Graue Literatur; Technischer Fortschritt; Performance-Messung; Medizinprodukteindustrie; EU-Staaten; new technology; medical device; health service; healthcare industry; investment; professional qualifications; big data; artificial intelligence; information security; advanced technology industry; report